Leadership questions for health care professionals : applying theories and principles to practice - Kutz, Matthew R. (Slack Incorporated, 2018)
"Leadership Questions for Health Care Professionals: Applying Theories and Principles to Practice by Dr. Matthew R. Kutz presents some of the most common leadership questions with the intent to facilitate intrigue and dialogue about the general concept of leadership and an awareness of potential leadership issues facing health care professionals. Leadership Questions for Health Care Professionals presents responses that will initiate discussion, as well as offer solutions based on the best available evidence across a wide spectrum of relevant research. Discussion questions at the end of each response will allow the reader to engage in critical thinking and re-evaluate their experiences and offer new insights into their leadership journey. Sections include questions on key issues for health care professionals: - The essence of leadership - Leadership development - Teamwork and communication - Change - Organizational culture and complexity - Leadership ethics and power - Diversity and multicultural leadership Instructors in educational settings can visit www.efacultylounge.com for additional materials to be used for teaching in the classroom. Leadership Questions for Health Care Professionals takes an interprofessional and interdisciplinary approach and is relevant for athletic trainers, physical therapists, occupational therapists, speech-language pathologists, nurses, physicians, and more. Leadership Questions for Health Care Professionals: Applying Theories and Principles to Practice offers students a broader conceptual understanding of leadership, as well as the depth required by seasoned health care clinicians, managers, and executives who are looking for practical and evidence-based insights to their toughest leadership issues"--Provided by publisher.